Presentation of Conditional Verbs in the Explanatory Dictionary (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines and analyzes conditional verbs in the explanatory dictionary. If we look at the history of language, we can see that lexical units with action and state are studied in two directions: from the point of view of lexical-semantic groups of lexemes and grammatical categories of word forms. In particular, the complex and diverse lexical-semantic classification of verbs in different languages creates a number of difficulties for language learners in mastering a particular language, determining the lexical meanings of words and their compatibility with other words. For this reason, this article analyzed the classification of action and state verbs in Uzbek linguistics, lexical-semantic groups from the point of view of world linguistics, and also made comments about their differences.